Perbandingan Administrasi Negara Indonesia Dengan Negara Selandia Baru - Sherly Anggraeni; Siswanto M, Djoko (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
The Comparative Study of State Administration contains relevant aspects, namely aspects of State Administration which contain a general understanding of how state institutions grow and live within a country to carry out their functions. State Administration is a concept that has various definitions. Referring to the agreement of the expert committee on state administration in the United Nations organization in order to equate a common perception on state administration, there are at least four different definitions of state administration (Committee of Experts on Public Administration, 2006). First, state administration as the organizer of government policies and programs as well as the behavior of employees (who are not politically elected) who formally have responsibility in carrying out the task of implementing these policies and programs. Second, state administration is all processes, organizations and individuals (who act in positions and have roles) related to the implementation of laws and other regulations issued by the legislature, executive and judiciary. From the definition above, an outline can be drawn, that state administration is not an executive, legislative, or judicial state institution, but rather, the overall implementation of what is decided by these state institutions in the context of administering public services. More precisely, state administration is the entire instrument of government institutions formed on the basis of law in the context of implementing public services, through its various dimensions covering the fields of management, budget, human resources, structure and procedures